Penerapan Teknik Search Engine Optimization (SEO) Dalam Produksi Berita Di Detik Sulsel - Melinda, Feni; Latief, Rahmawati; Muhammad, Firdaus; Mayasari Pakaya, Siti (Jambura Jurnal Ilmu Komunikasi, 2023)
Background: Online media is currently starting to adopt Search Engine Optimization (SEO) techniques as an instrument in producing news so that it can be in the top position of search engines. This is the case with Detik.Sulsel, which is one of the regional channels on the detik.com online media, which continues to experience an increasing trend in the number of online visitors. Purpose: This research aims to determine the application and flow of SEO techniques in detik.Sulsel news production at the on page and off page levels as well as to determine the supporting and inhibiting factors in implementing SEO techniques in detik.Sulsel. Methods: This research uses descriptive qualitative with data collection methods namely in-depth interviews, nonparticipant observation and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and drawing conclusions. Results: The results of this research show that SEO optimization at the on page level in detik.Sulsel has been implemented in accordance with SEO standards and emphasizes three main strategies in the news production process, namely content quality, credibility and relevance of articles created according to readers' needs. Detik.Sulsel always balances SEO and journalistic rules that must not be violated. At the off page level SEO optimization detik.Sulsel has also implemented special strategies such as internal links which are carried out only on internal detik.com, implementing an anchor article strategy, utilizing social media, and optimizing the available web analytics to the maximum. Conclutions: Then the research results also show that there are four supporting factors, namely an organized editorial system, meetings and evaluations, supporting advanced technology, and having article writing guidelines that apply SEO techniques. Implications: The inhibiting factor is that the Google algorithm is always changing, so SEO specialists must always follow and understand the latest algorithms.